Neonatal Morbidity in the Offspring of Obese Women Without Hypertension or Diabetes. Issue 4 (October 2018) - Polnaszek, Brock E.; Raghuraman, Nandini; Lopez, Julia D.; Frolova, Antonina L.; Wesevich, Victoria; Tuuli, Methodius G.; Cahill, Alison G.
Abstract : OBJECTIVE: To compare the independent risk of neonatal morbidity between the offspring of obese and nonobese women without hypertension or diabetes. METHODS: This is a secondary analysis of a prospective single-center cohort study of singleton deliveries at or beyond 37 weeks of gestation from 2010 to 2014. Women with diabetes (pregestational or gestational) and hypertensive disorders were excluded. The primary outcomes were 1) a composite neonatal morbidity including death, mechanical ventilation, respiratory distress, meconium aspiration, suspected sepsis, confirmed sepsis, hypoxic–ischemic encephalopathy, therapeutic hypothermia, or seizures; and 2) a composite of neonatal neurologic morbidity including hypoxic–ischemic encephalopathy, therapeutic hypothermia, or seizures. The primary outcomes were compared between the offspring of obese (body mass index 30 or greater) and nonobese women. Adjusted odds ratios (ORs) were estimated using multivariable logistic regression. RESULTS: Of 6, 458 women without diabetes or hypertensive disorders, 3, 311 (51%) were obese. After adjusting for race, neonates of obese patients were at significantly increased risk for the composite neonatal morbidity (9.2% vs 7.2%, adjusted OR 1.39, 95% CI 1.15–1.67) and neurologic neonatal morbidity (0.7% vs 0.3%, adjusted OR 2.84, 95% CI 1.22–6.65). Specifically, neonates of obese patients were more likely to have hypoxic–ischemic encephalopathy (0.5% vs 0.2%, adjusted OR 2.80, 95% CI 1.02–7.68), hypothermia treatment (0.6% vs 0.2%, adjusted OR 2.92 95% CI 1.17–7.30), and suspected sepsis (7.6% vs 5.8%, adjusted OR 1.45, 95% CI 1.18–1.79). CONCLUSION: In patients who labor, maternal obesity is an independent risk factor for significant neonatal morbidity, even in the absence of hypertensive disorders or diabetes. Abstract : Even in the absence of maternal hypertension or diabetes, the offspring of obese women are at increased risk of neonatal morbidity compared with the offspring of nonobese women.